Efektifitas Zakat Produktif Dalam Memberdayakan UMKM (Studi Kasus Pelaku UMKM di Pedan, Klaten, Jawa Tengah) - M Usman; Nur Sholikin (ITB AAS INDONESIA Surakarta, 2021)
Productive zakat is zakat given to a person or group of people to be used as working capital. Giving productive zakat to mustahik MSME actors is expected to help increase Mustahik's income so that it can reduce poverty levels. Productive zakat distribution at Baznas is expected to be able to alleviate poverty in society. In 2018, Pedan District was one of the areas selected by Baznas in distributing productive zakat to MSME players. This sub-district is located in Klaten Regency which has a position as one of the development centers of Klaten Regency. The majority of Pedan people work as MSME actors, so that if the potential of this community can be maximized it will reduce the level of poverty in the area. This research is a field research (field research). To achieve this goal the writer uses a qualitative descriptive approach. In this study, primary data was generated from interviews with mustahik who received assistance from Baznas. Meanwhile, secondary data is obtained from books, journals and related laws and regulations. The results showed that the distribution of productive zakat at Baznas to MSME players in Pedan has had a positive impact on increasing their business results as seen from the amount of mustahik income before and after receiving productive zakat calculated from the total net income of MSMEs after receiving assistance from Baznas, return or net profit received by mustahik in 2018 and 2019, the final capital analysis is calculated after the total liabilities and equity of MSME businesses, the level of capital growth (Pedan people) before and after receiving productive zakat